Amirullah Phenomenological Study of Quality of Life in Chronic Kidney Failure Patients Undergoing Hemodialysis - Amirullah; Astrid Nadifa Adil; A. Nurlaela Amin (Lembaga Penelitian dan Pengabdian Masyarakat Stikes Panrita Husada Bulukumba, 2023)
Background: Chronic Kidney Failure is a very serious health problem because it can affect morbidity, mortality and socio-economic conditions in society. One of the treatments for patients suffering from chronic kidney failure is hemodialysis. This therapy has various complications and requires patient compliance in undergoing therapy, this will have a physiological and psychological stressor impact on patients undergoing therapy which can then affect the quality of life of patients suffering from chronic kidney failure. Objective: To explore the quality of life of participants suffering from chronic kidney failure undergoing hemodialysis at H. Andi Sultan Daeng Radja Bulukumba Regional Hospital. Research Method: This research uses a qualitative design with a phenomenological study approach. Phenomenological research sample size is around 6-10 participants. So in this research, 10 participants were selected according to the criteria and recorded during in-depth interviews using a semi-structured interview guide, then interview transcripts were made and then analyzed using thematic analysis. Research Results: The research results identified eight main themes, namely: (1) Physical activity (2) Satisfaction with physical fitness during hemodialysis (3) Perception of conditions experienced during hemodialysis (4) Quality of sleep during hemodialysis therapy (5) Personal adaptation regarding physical changes (6) Social relationships (7) Changes in economic status during hemodialysis therapy (8) Spiritual response. Conclusions and suggestions: There are 8 themes obtained in this research. It is hoped that chronic kidney failure sufferers who undergo hemodialysis therapy will remain enthusiastic and increase their motivation to live, so that their quality of life will improve.